Epistemologi Pendidikan Seni Musik dalam Mencari Sumber dan Validitas Pengetahuan Musik - Hikmawati Usman; Abdullah Sinring; Anshari Anshari (DIDAKTIKA, 2025)
The epistemology of music art education discusses the source and validity of music knowledge in the context of learning and developing art science. This article explores how music knowledge is acquired, processed, and validated in art education. The epistemological approach includes various sources, such as aesthetic experience, music theory, performance practice, and cultural studies. In addition, the validity of music knowledge is measured through the criteria of objectivity, relevance, and consistency in the context of education. This article also highlights the importance of integration between local and universal traditions in building an inclusive and sustainable epistemological foundation. This research is expected to contribute to a deeper understanding of the process of forming music knowledge in art education.